RFLP Marker Variation of Cytocrome b Gene and Genetic Relationship among Batur, Merino and Local Sheep Breeds - Prayitno, Prayitno; Hartati, T; Pratiwi, R; Artama, WT (ANIMAL PRODUCTION, 2011)
RFLP analysis of mitochondrial DNA cytochrome b gene was conducted to determine the diversity, status and close genetic relationships in a population of Batur sheep with the Merino and local sheep breeds (Garut, Thin Tail and Fat Tail). The research used genomic DNA of 27 samples of Batur, 15 Merino, 17 Garut, 15 Thin Tails and 15 Fat Tails sheep. The PCR process used two types of 25 nucleotides primers. The PCR products were checked by using 2% agarose gel electrophoresis. The PCR DNA fragment was digested by using Hae III at 37 oC and incubated for 10 hours. Similarities and differences of cytochrome b gene RFLP bands between individual samples of one and across populations, genetic distance, and close genetic relationship, were identified. The PCR process of the cytochrome b gene metochondrial DNA of the 45 samples of sheep yielded 359 bp band types. The digestion (cutting) of the PCR products of mitochondrial DNA cytochrome b gene by using Hae III resulted in RFLP band profiles of 128 up to 231 bp polymorphisms of cytochrome b gene. Although the Hae III restriction enzyme recognized only one restriction site, however, between samples of Batur, Merino, Garut, Thin Tail, and Fat Tails, there were monomorphism and polymorphism Hae III loci.Key Words: Â RFLP, cytochrome b gene, genetic markers, genetic similarity, Batur sheeAnimal Production 13(3):156-165 (2011)Â